Teaching and learning in the early years - Whitebread, David 1948-; Coltman, Penny (Routledge, 2015)
"This best-selling text book provides a broad-ranging and up-to-date review of thinking and best practice within nursery and infant education. Written around the basic truth that an effective early years curriculum must start with the children, their needs and their potential, the contributors to this classic text acknowledge that learning must have a strong element of fun, wonder and excitement. Fully revised and updated in light of recent changes to the Early Years curriculum, with brand new chapters on assessment, communication, writing, creativity and diversity, the contributors address a range of fundamental issues and principles, including: - an analysis of research into how children learn; - discussions of issues such as classroom organisation, curriculum management, and assessment; - a detailed section on play and language; - chapters covering individual curriculum areas, including new chapters on music and PSHE. Each chapter combines a review of important principles with practical and inspiring classroom examples throughout. It is essential reading for all Foundations Stage and KS1 trainee teachers, their tutors and mentors, and serving teachers working in the 3-7 age range who wish to reflect upon and develop their practice"--Provided by publisher.